2017
DOI: 10.1186/s12885-017-3222-8
|View full text |Cite
|
Sign up to set email alerts
|

Negative lymph node count is an independent prognostic factor for patients with rectal cancer who received preoperative radiotherapy

Abstract: BackgroundNegative lymph node (NLN) count has been reported to provide more accurate prognostic information than the N stage alone in patients with rectal cancer (RC). Since preoperative radiotherapy (Pre-RT) can significantly affect the LN status, it is unclear whether NLN count still has prognostic value count on survival of patients with RC who received Pre-RT.MethodsIn this study, clinicopathological characteristics, number of positive LNs and survival time were collected from Surveillance, Epidemiology, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 17 publications
2
17
1
Order By: Relevance
“…Recently, LN count drew the attention to assess their impact on the cancer recurrence and OS [11]. Moreover, many researchers have shown the prognostic role of examined (dissected) LNs (ELNs) [12-14], positive (metastatic) LNs (PLNs) [15], negative LNs (NLNs), and LN ratio (LNR) in different cancer types including esophageal, thyroid, cervical, and lung cancers [16]. NLN count has been reported to provide more accurate prognostic information than the N stage alone in patients with rectal cancer [12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, LN count drew the attention to assess their impact on the cancer recurrence and OS [11]. Moreover, many researchers have shown the prognostic role of examined (dissected) LNs (ELNs) [12-14], positive (metastatic) LNs (PLNs) [15], negative LNs (NLNs), and LN ratio (LNR) in different cancer types including esophageal, thyroid, cervical, and lung cancers [16]. NLN count has been reported to provide more accurate prognostic information than the N stage alone in patients with rectal cancer [12].…”
Section: Introductionmentioning
confidence: 99%
“…Rectal cancer (RC), one of the most commonly diagnosed malignant tumors, is a crucial threat imperiling human health worldwide. 1 2016 cancer statistics report indicated approximately 39220 new RC cases in the United States and estimated incidence of 11 per 100000 people in the developing countries. 2 3 Despite of great improvement in early diagnosis, operative treatment, adjuvant therapies (such as chemotherapy, radiotherapy and hormonotherapy) and integrated patients' care, the prognosis of RC patients remains far from satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…However, eight negative LNs is not a minimum number according to our study. We used X‐Tile model to identify the appropriate number which have been applied by other studies (Huang et al, ; Li et al, ; Spillane, Haydu, McMillan, Stretch, & Thompson, ). Our results demonstrated that the optimal cut‐off value for negative LNs dissection was five in patients with high‐risk group, and patients with >5 negative LNs dissection had a significantly higher CSS than those with ≤5 negative LNs dissection.…”
Section: Discussionmentioning
confidence: 99%